AKRON BRASS MANUFACTURING COMPANY, INC.: REORGANIZATION; APPRECIATION OF FIXED ASSETS; PARENT AND UNPROFITABLE SUBSIDIARY. - Fisher, Allan J. (The Accounting Review, 1940)
Abstract The article presents accounting cases of Akron Brass Manufacturing Co. Inc. The history of the Akron Brass Manufacturing Co. Inc. presents some rather interesting features in conjunction with a very simple reorganization, the appreciation of fixed assets and a brief experience with a single, unprofitable subsidiary. The company was organized in Ohio on July 6, 1935, to take over the business of The Akron Brass Manufacturing Co. The latter had been incorporated on December 26, 1919 and continued as a going concern until July 8, 1935, when all of its assets were transferred to; and all of its liabilities assumed by, the Akron Brass Manufacturing Co. Inc. The Akron Brass Manufacturing Co. Inc. is principally engaged in the manufacture, sale and assembly of brass and alloy goods for fire and mill equipment. The company's products include nozzles, hose couplings, siphons, coupling expanders; fire hose test pumps and other fire fighting equipment. An abortive attempt to expand its activities through a wholly owned subsidiary was made in 1937. The balance sheet of the company prior to the reorganization is presented in the article.